1989
DOI: 10.1002/app.1989.070370121
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of poly(3,3‐bisethoxymethyl oxetane) and poly(3,3‐bisazidomethyl oxetane) and their block copolymers

Abstract: SynopsisThe homopolymers, poly(3,3-bisethoxymethyl oxetane) (polyBEMO), poly(3,3-bisazidomethyl oxetane) (polyBAMO), and triblock copolymers based on these homopolymers and a statistical copolymer center block composed of BAMO and 3-azidomethyl-3-methyl oxetane AMMO were synthesized and characterized by differential scanning calorimetry, modulus-temperature, optical microscopy, membrane osmometry, and solution and melt viscosity. The values of K and a for the Mark-Houwink equation were found to be 7.29 x mL/g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The viscoelastic behavior of polyBEMO block copolymers was investigated by Hardenstine The phenomenon of multiple melting peaks was initially observed for polyBEMO by Hardenstine et a1.21 and then by E. A. Murphy et al 24 In both studies, multiple melting phenomena were observed only for samples crystallized from the polymerization vessel, not for samples crystallized from the melt or from solution. In the present paper, the presence of multiple melting peaks in polyBEMO samples crystallized from the melt is characterized.…”
Section: Introductionmentioning
confidence: 97%
“…The viscoelastic behavior of polyBEMO block copolymers was investigated by Hardenstine The phenomenon of multiple melting peaks was initially observed for polyBEMO by Hardenstine et a1.21 and then by E. A. Murphy et al 24 In both studies, multiple melting phenomena were observed only for samples crystallized from the polymerization vessel, not for samples crystallized from the melt or from solution. In the present paper, the presence of multiple melting peaks in polyBEMO samples crystallized from the melt is characterized.…”
Section: Introductionmentioning
confidence: 97%
“…1,2 In view of the inherent disadvantages of cross-linked polymers and energy, a profound interest has emerged concerning the development of energetic thermoplastic elastomers (ETPEs) as a suitable candidate for binder applications. 3,4 Hence, a considerable amount of work has been devoted to investigating ETPEs binder and ETPE-based propellant, which show good application prospects for propellant. [5][6][7][8][9] During the past decades, glycidyl azide polyol ETPE (GAP-ETPE)-based propellant is extensively studied not only because of its high energy, insensitivity and greenness, environment-friendliness and recyclability but also for its simple screw processing and high productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional binders use crosslinked elastomers, in which prepolymers (e.g., HTPB) are crosslinked by chemical curing/crosslinking agents. However, the disposal of the crosslinked binder is difficult and usually accomplished by burning; this causes environmental problems . In view of the inherent disadvantages of crosslinked polymers, there has been profound interest in the development of thermoplastic elastomers (TPEs) as suitable candidates for binder applications.…”
Section: Introductionmentioning
confidence: 99%